Research and Implementation of Massive Design Documents on Distributed Storage ＆ Load Balancing - Liliang Su; Yunfu Wang; Bin Hou (Dianxin kexue)
The most suitable system architecture was presented, based on the distributed storage and load balancing, after the analysis and comparison of the technology of massive design documents in distributed storage. The solution avoids user taking a long wait to access storage resources, breaks the bandwidth bottleneck of enterprise Web application in the LAN, reduces the burden on central storage, and achieves the global load balancing between Web application and distributed storage, so as to ensure the high availability of system.